Long-Term Effects of Ozone Treatment in Patients with Persistent Numbness and Tingling Secondary to Chemotherapy-Induced Peripheral Neuropathy. A Retrospective Study - Bernardino Clavo MD, PhD; Delvys Rodríguez-Abreu MD, PhD; Saray Galván-Ruiz MD; Mario Federico MD, PhD; Angeles Cánovas-Molina RN; Yolanda Ramallo-Fariña MSc; Carla Antonilli MD; Gretel Benítez MD; Himar Fabelo BEng MSc, PhD; Carla García-Lourve RN, MRes; Damián González-Beltrán CNS, MSc; Ignacio J. Jorge MD, PhD; et al. (Integrative Cancer Therapies)
Background: Numbness and tingling secondary to chemotherapy-induced peripheral neuropathy (CIPN) are frequent side effects that limit chemotherapy treatment and quality of life. Successful treatments for CIPN are limited. This preliminary report shows the potential long-term effects of ozone treatment in the management of persistent numbness and tingling secondary to CIPN. Methods: Ozone treatment was administered by rectal insufflation in 15 patients (female/male: 8/7, age: 66 years old) suffering from persistent numbness and tingling secondary to grade-2 or grade-3 CIPN. Planned ozone treatment consisted of 40 sessions over 4 months. The initial concentration of 10 μg/mL was progressively increased to 30 μg/mL. The initial gas volume of 180 mL/session was progressively increased to 300 mL/session if tolerated. Before and after ozone treatment, and at 3- and 6- months after the end of treatment, they were assessed (i) the grade of CIPN-toxicity, and (ii) the self-reported decrease in numbness and tingling. Results: After ozone treatment, 47% of patients experienced a decrease in the grade of CIPN-toxicity ( P  = .016), and 67% of patients reported a decrease in numbness and tingling ≥50% ( P  = .002). These effects were maintained at 3- and 6- months after the end of O 3 T. Conclusions: In this retrospective report, patients with persistent numbness and tingling secondary to CIPN showed clinically relevant and long-term improvements after ozone treatment. The magnitude and duration of the observed effects merit further research and support our ongoing clinical trials.